Observing the Craft of Mentoring Students During the Year Abroad - Lesley Harbon (PORTAL: Journal of Multidisciplinary International Studies)
As a senior university manager overseeing targeted study abroad programs in the Bachelor of Arts in International Studies (BAIS) at the University of Technology Sydney (UTS), I had the opportunity to accompany Associate Professor Ilaria Vanni-Accarigi on a Block Visit to our students in Italy. This experience deepened my understanding of the nuanced pedagogical approaches that support students’ successful international experiences, highlighting the significance of place, time and the intuitive teacher-student relationship in fostering intercultural learning.